Emancipation: a given concept? Dialogues with Rural Education - Lia Machado dos Santos; Luci Mary Duso Pacheco (Universidade Federal do Norte do Tocantins, 2024)
The article reflects how the concept of emancipation has been exposed in academic research in Brazil and carries out a dialogue between emancipation and Rural Education. For this, a survey of theses and dissertations defended between 2012 and 2022 was carried out. In all, 33 works were selected, in which theoretical choices were analyzed, as well as an analysis of scientific rigor from Charlot (2006). The study revealed a portion of studies in education that use the term emancipation without its conceptualization, in dialogue with Rural Education, the scarcity of emancipatory projects in the dispute for public policies is perceived.